Ultrasound-guided percutaneous drainage as an alternative to surgery in treating breast abscesses - Karaca, Rukan; Topal, Uğur; Nas, Ömer Fatih; Gökalp, Gökhan; Taşdelen, İsmet and Dündar, Halit Ziya (The European Research Journal, 2019)
Objectives: The aim of this study was to assess whether ultrasound-guided (US-guided) percutaneous drainage of breast abscesses could be used as an alternative to surgery. Methods: We performed a retrospective study. Twenty patients were included in the study who were diagnosed as having a non-specific breast abscess. Eleven patients underwent surgery whereas nine patients were treated with US-guided drainage. Ultrasonographic findings, results of treatment and follow-up were evaluated between the two groups. Results: In the US-guided drainage group, 5 patients were treated with needle aspiration and 4 were treated with catheter drainage. All cases within the needle aspiration group totally recovered. However, one case within the catheter drainage group failed. The total success rate of US-guided drainage was 88.8%. The median follow-up period was 21.0 days in the US-guided drainage group and 45.0 days in the surgical drainage group. There were no statistically significant differences in terms of recovery (p = 0.450) and follow-up periods (p = 0.112) between the surgical drainage and US-guided drainage groups. Conclusions: US-guided percutaneous drainage may be preferred as a first method of choice in treatment of a breast abscess. The most appropriate approach to breast abscess treatment will be possible with a multidisciplinary approach of surgery and radiology.